2017
DOI: 10.3389/fcimb.2017.00468
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Two-component System LytSR Affects Forespore Engulfment in Bacillus thuringiensis

Abstract: Two-component regulatory systems (TCSs) play pivotal roles in bacteria sensing many different stimuli from environment. Here, we investigated the role of the LytSR TCS in spore formation in Bacillus thuringiensis (Bt) subsp. kurstaki HD73. lacZ gene fusions revealed that the transcription of the downstream genes, lrgAB, encoding two putative membrane-associated proteins, is regulated by LytSR. The sporulation efficiency of a lytSR mutant was significantly lower than that of wild-type HD73. A confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Confocal laser-scanning microscopy was performed as previously described [23]. Briefly, cells were stained with the membrane dye FM4-64 (final concentration 100 µM; Molecular Probes, Inc., Eugene, OR, USA).…”
Section: Confocal Laser-scanning Microscopymentioning
confidence: 99%
“…Confocal laser-scanning microscopy was performed as previously described [23]. Briefly, cells were stained with the membrane dye FM4-64 (final concentration 100 µM; Molecular Probes, Inc., Eugene, OR, USA).…”
Section: Confocal Laser-scanning Microscopymentioning
confidence: 99%
“…A comparison of the amino acid sequences of available LrgA homologs revealed that LrgA (HD73_RS29150) of B. thuringiensis HD73 shares 62%, 99%, and 100% similarity with LrgA (YsbA, BSU28910) of B. subtilis 168, LrgA (BC5439) of B. cereus ATCC 14579, and LrgA (BA5690) of B. anthracis Ames, respectively. In our previous study, we found that deletion of lrgAB did not significantly affect sporulation efficiency by the method of heating cells for elimination of non-sporulating cells [44]. In this study, we directly counted the number of sporulating cells in the microscopy images.…”
Section: Discussionmentioning
confidence: 91%
“…A 1032-bp fragment preceding the start codon of cdsR (cdsR fragment A) was amplified by PCR, utilizing HD73 genomic DNA as the template and cdsR-AF and cdsR-AR as the forward and reverse primers, respectively. Furthermore, the primers cdsR-BF and cdsR-BR were used to amplify a 1015-bp fragment downstream of the 96th codon of cdsR (cdsR fragment B), whereas the primers cdsR-KmF and cdsR-KmR were utilized to amplify a 1473-bp kanamycin resistance gene cassette (kana) derived from pMAD-ΔlrgAB [44] plasmid. The cdsR A, kana, and cdsR B fragments were ligated through overlapping PCR using the primers cdsR-AF and cdsR-BR.…”
Section: Construction Of the Cdsr Deletion Mutantmentioning
confidence: 99%
See 1 more Smart Citation
“…The vital membrane dye FM 4-64 (Molecular Probes, Inc., Eugene, OR, USA) or MitoTracker green FM (ThermoFisher, USA) was dissolved in dimethyl sulfoxide ( 35 ). To assess polar septa and engulfment, 1-ml amounts of cells cultured to a designated time point in SSM medium were pelleted and resuspended in 0.02 to 0.05 ml H 2 O. Aliquots (2 μl) of the cell suspensions were placed on slides, stained with FM 4-64 (100 μM) and MitoTracker green FM (MTG; 100 nM) for 1 min ( 47 ), and then scanned with a confocal laser scanning microscope (Leica TCS SL; Leica Microsystems, Wetzlar, Germany) ( 24 ). Each strain was scanned independently at least three times, and each scan was then viewed in at least five fields.…”
Section: Methodsmentioning
confidence: 99%